Speed and agility training for baseball/softball - Magrini, M.; Dawes, J. J.; Spaniol, F. J.; Roberts, A. (Strength and Conditioning Journal, 2018)
In the sports of baseball and softball, power, speed, and agility are essential characteristics for success. Players who possess these characteristics may be able to cover a larger portion of the field and react to specific situations while running on the base paths. It is essential that the coach or strength and conditioning professional conduct drills that are sports-specific to the game of baseball or softball. The following article discusses the baseball/softball players' needs and provides recommendations for potential sport-specific drills that can be completed in an indoor facility or on the baseball/softball field.